“Turning rivers into milk and honey”: four testimonies about youth and left-wing political culture in Costa Rica (1970s and 1980s) - Brenes Valverde, Kevin (2024)
This article analyzes the involvement of four young Costa Ricans with left-wing political organizations in Costa Rica. These individuals also actively participated in revolutionary armed struggles in the Central American region during the 1970s and 1980s. Through a biographical-narrative method, their processes of engagement with political organizations are examined, focusing on aspects such as: the acquisition of consciousness, youth socialization spaces, cultural products, political training spaces, and political actions. This process constituted and reproduced a political culture inclined towards radicalization, which informed their practices and gave them meaning.